INTERMEDIATE AND LONG TERM OUTCOME OF PATIENTS AFTER DEVICE CLOSURE OF ASD WITH SPECIAL REFERENCE TO COMPLICATIONS - Kazmi, Tehmina; Sadiq, Masood; Rehman, Asif -ur-; Hyder, Najam; Latif, Farhan (Journal of Ayub Medical College Abbottabad, 2009)
Background: Device closure of Secundum atrial septal defect (ASD) is an accepted mode of treatment in selected patients with a suitable defect. The major initial concern over the long term outcome has been erosions and more recently development of aortic regurgitation. Objective was to assess the intermediate and long term outcome of patients with device closure of ASD with special reference to complications. Methods: Two hundred and four patients with significant Secundum ASD, 16 months to 55 years (median 8 years) were considered for transcatheter closure with the Amplatzer septal occluder from October 1999 to April 2009 with follow up examinations at 1, 3, 6, and 12 months and thereafter at yearly interval. Results: Device closure of ASD was done successfully in 202/204 patients. The immediate (first 24-hour) major complications included device embolization (n=4), pericardial effusion (n=1) and 2:1 heart block (n=1). At a mean follow up of 4.9 years (90 days to 9.6 years, median 5.3 years) complete closure was documented in all patients. Two patients (1%) had developed mild aortic regurgitation. Atrial fibrillation occurred in 3 adult patients (1.5%) at a mean of 2 weeks post procedure with complete recovery within 6 months. There were no late embolizations, erosions or thromboembolic events on long term follow up. Conclusions: Device closure of Secundum ASD using Amplatzer septal occluder is safe and effective in intermediate and long term follow up with extremely low mortality rate. The risk of development of aortic regurgitation or atrial fibrillation is also very low. Keywords: Atrial septal defect, Device closure, Cardiac catheterisation, Complications